Peningkatan Kemampuan Bahasa Ekspresif Melalui Kegiatan Gambar Ekspresi Bebas Di PAUD - Supinah, Susi; Ksih, Delina; Suhardjo, Sudi (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Improving Expressive Language Ability through Expressive Drawing Activities for children aged 5-6 years at PAUD Nurul Hikmah. Thesis. Bekasi: Panca Sakti University Bekasi. 2024. This research aims to determine the increase in expressive language skills of children aged 5-6 years through Free Expression Drawing activities at PAUD Nurul Hikmah. This research uses a classroom action research method that analyzes learning activities that use strategies to achieve the expected increase in learning abilities. The research method used aims to improve children's achievements by improving the learning process gradually during the research. This classroom action research was carried out through a pre-cycle and two cycles with Free Expression drawing activities to improve the expressive language skills of children aged 5-6 years, where each cycle consisted of planning activities, action implementation, observation and reflection. The subjects of this research were group B children with an age range of 5-6 years. The results of the research show that free expressive drawing activities can improve children's ability to express language or what is often known as expressive language ability in children aged 5-6 years at Paud Nurul Hikmah, namely pre-cycle results of 34.17%; cycle I 51.25% and cycle II 80%. The results of this research provide meaning with an increase from pre-cycle to cycle 2, showing that free expression drawing activities can increase the expressive language abilities of children aged 5-6 years by 80%, which shows the success of this action because the minimum completeness criterion is 75%